Method for improving mineralized collagen performance based on discrete increase of ion concentration

By dynamically controlling the ion concentration to simulate the natural bone mineralization process, mineralized collagen that is more consistent with the real bone structure was prepared, which solved the problem of insufficient mineral morphology and mechanical properties in the existing technology and realized the preparation of multi-scale biomimetic bone matrix materials.

CN121102586AActive Publication Date: 2025-12-12BEIJING UNIV OF TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202511345550.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-19
Publication Date
2025-12-12
Estimated Expiration
2045-09-19

AI Technical Summary

Technical Problem

Existing technologies fail to effectively simulate the dynamic ion concentration changes in real bone when preparing mineralized collagen, resulting in mineral morphology that differs from real bone and insufficient mechanical properties.

Method used

By dynamically controlling the ion concentration, the nonlinear process of natural bone mineralization is simulated, and a dynamically mineralized collagen solution is prepared and freeze-dried to form a scaffold with dynamically changing ion concentration, thereby increasing the amount of minerals attached.

Benefits of technology

It improves the degree of mineralization at the micron scale and enhances the mechanical properties of mineralized collagen at the macro scale, approaching the structural properties of natural bone.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121102586A_ABST
    Figure CN121102586A_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving mineralized collagen performance based on discrete increase of ion concentration, and belongs to the technical field of biological material preparation, and the method comprises the following steps: step 1, preparing a reaction stock solution; 2, preparing a dynamically mineralized collagen solution; and step 3, preparing the bracket with dynamically changed ion concentration. According to the method for improving the performance of the mineralized collagen based on discrete increase of the ion concentration, the nonlinear process of mineralization of natural bones is simulated by dynamically regulating and controlling the ion concentration, more inorganic minerals can be attached to the collagen, and the mineralization degree of the prepared collagen is higher on the micron scale; on the macroscopic scale, the mechanical property of the mineralized collagen is better, the mineral substances are more, and the technical support can be provided for preparing the multi-scale bionic bone matrix material.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of biomaterial preparation, in particular to a method for improving the performance of mineralized collagen based on the increase of ion concentration dispersion. BACKGROUND

[0002] Bone matrix is formed by the organic collagen and inorganic hydroxyapatite through biomimetic mineralization, and collagen mainly bears deformation to provide toughness for mineralized collagen, and minerals mainly bear stress to provide strength for mineralized collagen. Mineralized collagen has a good prospect in clinical application of bone repair due to its good biocompatibility and high consistency with the composition of bone matrix. However, the mechanical properties of the prepared mineralized collagen are insufficient, that is, the minerals mainly bearing stress are insufficient, and therefore how to improve the mechanical properties of mineralized collagen, that is, how to improve the minerals, is the key and difficulty of research. In the real bone mineral formation process, the ion concentration is not constant, but dynamic, and the mineralized collagen prepared by constant ion concentration and dynamic ion concentration change has different forms. At present, mineralized collagen has been prepared by using different chemical and physical environments, but these studies do not consider the dynamic ion mineralization process, so that the mineral form is different from the real bone, and the mineralized collagen with mechanical properties consistent with the real bone structure has not been prepared. SUMMARY

[0003] The purpose of the present application is to provide a method for improving the performance of mineralized collagen based on the increase of ion concentration dispersion, which can simulate the nonlinear process of natural bone mineralization by dynamically regulating the concentration of ions to enable collagen to attach more inorganic minerals, and the prepared mineralization degree is higher on the micron scale, and the mechanical properties of the mineralized collagen are better on the macro scale, and the minerals are more, which can provide technical support for the preparation of multi-scale biomimetic bone matrix materials.

[0004] In order to achieve the above purpose, the present application provides a method for improving the performance of mineralized collagen based on the increase of ion concentration dispersion, comprising the following steps:

[0005] Step one, preparing a reaction stock solution;

[0006] Step two, preparing a dynamically mineralized collagen solution;

[0007] Step three, preparing a scaffold with dynamic ion concentration change.

[0008] Preferably, the reaction stock solution in step one comprises calcium chloride, diammonium hydrogen phosphate, NaOH solution and collagen stock solution, wherein the concentration of calcium chloride is 0.5-1 mol / L, the concentration of diammonium hydrogen phosphate is 0.5-1 mol / L, the concentration of NaOH is 0.1-1 mol / L, and the collagen stock solution is type I collagen with a concentration of 1-5 w%.

[0009] Preferably, the specific operation of step two is as follows: add calcium chloride and diammonium hydrogen phosphate solution to type I collagen stock solution for mineralization, repeat 2-4 times, each time adding the same amount of calcium chloride and diammonium hydrogen phosphate solution, and adjust the pH with NaOH solution. After stirring thoroughly, centrifuge to collect the composite material, discard the supernatant, and obtain the mineralized collagen solution.

[0010] Preferably, the specific operation of step three is as follows: take the lower layer of mineralized collagen solution, shake it evenly, drop it into the mold, freeze-dry it in the refrigerator to form a shape, and then freeze-dry it in a freezer vacuum machine to obtain a scaffold with dynamic ion changes.

[0011] Preferably, in step two, the amount of type I collagen stock solution used is 5-10 mL, and the amount of calcium chloride and diammonium hydrogen phosphate solution added each time is 2-5 mL. Each time calcium chloride and diammonium hydrogen phosphate solution is added, mineralization is required for 1-2 hours. The pH is adjusted to 7-8 with NaOH solution, and after thorough stirring, it is kept for 1-2 hours. The volume is then adjusted to 10-15 mL, and it is kept at pH 7-8 for 36-48 hours. After mineralization is completed, centrifugation is performed at a speed of 4000-6000 rpm.

[0012] Preferably, in step two, when adjusting the pH, a high-concentration NaOH solution is first used for coarse adjustment, and then a low-concentration NaOH solution is used for fine adjustment.

[0013] Preferably, in step three, the temperature in the refrigerator is -15 to -20°C, and the freeze-drying time is 24-36 hours, or the freeze-drying time is 24-36 hours in a freezer vacuum machine.

[0014] Therefore, the present invention employs the above-mentioned method for improving the properties of mineralized collagen based on discretely increasing ion concentration, which has the following beneficial effects:

[0015] (1) Compared with the traditional single ion concentration mineralization method, the present invention fully considers the influence of dynamic ion concentration, i.e. the mineralization process of the material, on mineralization and constructs a dynamic ion mineralization system, which can better simulate the complex mineralization process in real bone and prepare bone matrix materials that are more in line with the real bone structure.

[0016] (2) By dynamically adjusting the concentration of ions, the nonlinear process of natural bone mineralization was simulated, which enabled collagen to attach more inorganic minerals. At the micron scale, the prepared mineralization degree was higher. At the macro scale, the mineralized collagen had better mechanical properties and more minerals, which can provide technical support for the preparation of multi-scale biomimetic bone matrix materials.

[0017] (3) The prepared material has undergone multi-scale and multi-level mineralization, and has stronger mechanical properties and compatibility than traditional mineralized collagen.

[0018] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description

[0019] Figure 1 This is a flowchart of the preparation of Examples 1-3 and Comparative Examples 1-2 of the present invention, which describes a method for improving the performance of mineralized collagen based on discretely increasing ion concentration.

[0020] Figure 2 These are SEM images of Examples 1-3 and Comparative Examples 1-2 of the present invention, which describe a method for improving the performance of mineralized collagen based on discretely increasing ion concentration.

[0021] Figure 3 These are Young's modulus diagrams of Examples 1-3 and Comparative Examples 1-2 of the present invention, which describe a method for improving the properties of mineralized collagen based on discrete increases in ion concentration.

[0022] Figure 4 These are Fourier transform infrared spectra of Examples 1-3 and Comparative Examples 1-2 of the present invention, which describe a method for improving the performance of mineralized collagen based on discretely increasing ion concentration. Detailed Implementation

[0023] The technical solution of the present invention will be further described below with reference to the accompanying drawings and embodiments.

[0024] Unless otherwise defined, the technical or scientific terms used in this invention shall have the ordinary meaning as understood by one of ordinary skill in the art to which this invention pertains.

[0025] This invention provides a method for improving the properties of mineralized collagen based on discretely increasing ion concentration, comprising the following steps:

[0026] Step 1: Prepare the reaction stock solution: The reaction stock solution includes calcium chloride, diammonium hydrogen phosphate, NaOH solution, and collagen stock solution. The concentration of calcium chloride is 0.5-1 mol / L, the concentration of diammonium hydrogen phosphate is 0.5-1 mol / L, the concentration of NaOH is 0.1-1 mol / L, and the collagen stock solution is type I collagen with a concentration of 1-5 wt%.

[0027] Step 2: Preparation of dynamically mineralized collagen solution: Add 4-5 mL of calcium chloride and diammonium hydrogen phosphate solution to 5-10 mL of type I collagen stock solution. After mineralizing for 1-2 hours, add another 4-5 mL of calcium chloride and diammonium hydrogen phosphate solution. Adjust the pH to 7-8 using NaOH solution, first using a high-concentration NaOH solution for coarse adjustment, then using a low-concentration NaOH solution for fine adjustment. Stir thoroughly for 1-2 hours, then bring the volume to 10-15 mL and maintain the solution at pH 7-8 for 36-48 hours. Afterward, centrifuge at 4000-6000 rpm to collect the composite material, discard the supernatant, and obtain the mineralized collagen solution.

[0028] Step 3: Preparation of scaffold with dynamic ion concentration: Take the lower layer of mineralized collagen solution, shake it evenly, drop it into a mold, and freeze-dry it in a refrigerator at -15 to -20°C for 24-36 hours to form a shape. Then freeze-dry it in a freezer vacuum machine for 24-36 hours to obtain the scaffold with dynamic ion concentration.

[0029] Example 1

[0030] like Figure 1 As shown, this invention provides a method for improving the properties of mineralized collagen based on discretely increasing ion concentration, comprising the following steps:

[0031] Step 1: Preparation of the reaction stock solution: The reaction stock solution includes calcium chloride, diammonium hydrogen phosphate, NaOH solution, and collagen stock solution. The concentration of calcium chloride is 1 mol / L, the concentration of diammonium hydrogen phosphate is 0.6 mol / L, the concentration of NaOH is 0.1 mol / L and 1 mol / L, and the collagen stock solution is bovine Achilles tendon type I collagen purchased from Chengdu Kele Biological Products Co., Ltd., which is the collagen reaction stock solution with a concentration of 2w%.

[0032] Step 2: Preparation of dynamically mineralized collagen solution: Add 4.2 mL of calcium chloride and diammonium hydrogen phosphate solution to 5 mL of 2% type I collagen stock solution. After mineralizing for 1 h, add another 4.2 mL of calcium chloride and diammonium hydrogen phosphate solution. Adjust the pH to 7.4 using NaOH solution, first coarsely adjusting with 1 mol / L NaOH solution, then finely adjusting with 0.1 mol / L NaOH solution. Stir thoroughly and maintain for 1 h. Make up to 14 mL and maintain at pH 7.4 for 48 h. Then, centrifuge at 5000 rpm to collect the composite material, discard the supernatant, and obtain the mineralized collagen solution.

[0033] Step 3: Preparation of scaffold with dynamic ion concentration: Take the lower layer of mineralized collagen solution, shake it evenly, drop it into the mold, freeze-dry it at -20℃ for 24 hours to form the scaffold, and then freeze-dry it in a freezer vacuum machine for 24 hours to obtain the scaffold with dynamic ion concentration.

[0034] Example 2

[0035] This invention provides a method for improving the properties of mineralized collagen based on discretely increasing ion concentration, comprising the following steps:

[0036] Step 1: Preparation of the reaction stock solution: The reaction stock solution includes calcium chloride, diammonium hydrogen phosphate, NaOH solution, and collagen stock solution. The concentration of calcium chloride is 1 mol / L, the concentration of diammonium hydrogen phosphate is 0.6 mol / L, the concentration of NaOH is 0.1 mol / L and 1 mol / L, and the collagen stock solution is bovine Achilles tendon type I collagen purchased from Chengdu Kele Biological Products Co., Ltd., which is the collagen reaction stock solution with a concentration of 2w%.

[0037] Step 2: Preparation of dynamically mineralized collagen solution: Add 2.1 mL of calcium chloride and diammonium hydrogen phosphate solution to 5 mL of 2% type I collagen stock solution. Mineralize for 1 h, then add another 2.1 mL of calcium chloride and diammonium hydrogen phosphate solution and mineralize for another h. Repeat this process four times. Adjust the pH to 7.4 using NaOH solution, first coarsely adjusting with 1 mol / L NaOH solution, then finely adjusting with 0.1 mol / L NaOH solution. Stir thoroughly and maintain for 1 h. Make up the volume to 14 mL and maintain at pH 7.4 for 48 h. Then centrifuge at 5000 rpm to collect the composite material, discard the supernatant, and obtain the mineralized collagen solution.

[0038] Step 3: Preparation of scaffolds with dynamic changes in ion concentration: According to the progress of collagen cross-linking and collagen mineralization, after mineralization for 12 hours, the scaffolds are frozen at -20°C and then freeze-dried after 24 hours of freezing.

[0039] Example 3

[0040] This invention provides a method for improving the properties of mineralized collagen based on discretely increasing ion concentration, comprising the following steps:

[0041] Step 1: Preparation of the reaction stock solution: The reaction stock solution includes calcium chloride, diammonium hydrogen phosphate, NaOH solution, and collagen stock solution. The concentration of calcium chloride is 1 mol / L, the concentration of diammonium hydrogen phosphate is 0.6 mol / L, the concentration of NaOH is 0.1 mol / L and 1 mol / L, and the collagen stock solution is bovine Achilles tendon type I collagen purchased from Chengdu Kele Biological Products Co., Ltd., which is the collagen reaction stock solution with a concentration of 2w%.

[0042] Step 2: Preparation of dynamically mineralized collagen solution: Add 2.1 mL of calcium chloride and diammonium hydrogen phosphate solution to 5 mL of 2% type I collagen stock solution. Mineralize for 1 h, then add another 2.1 mL of calcium chloride and diammonium hydrogen phosphate solution and mineralize for another h. Repeat this process twice. Adjust the pH to 7.4 using NaOH solution, first coarsely adjusting with 1 mol / L NaOH solution, then finely adjusting with 0.1 mol / L NaOH solution. Stir thoroughly and maintain for 1 h. Make up the volume to 14 mL and maintain at pH 7.4 for 48 h. Then centrifuge at 5000 rpm to collect the composite material, discard the supernatant, and obtain the mineralized collagen solution.

[0043] Step 3: Preparation of scaffolds with dynamic changes in ion concentration: According to the progress of collagen cross-linking and collagen mineralization, after mineralization for 12 hours, the scaffolds are frozen at -20°C and then freeze-dried after 24 hours of freezing.

[0044] Comparative Example 1

[0045] A method for improving the properties of mineralized collagen based on discretely increasing ion concentration includes the following steps:

[0046] Step 1: Preparation of the reaction stock solution: The reaction stock solution includes calcium chloride, diammonium hydrogen phosphate, NaOH solution, and collagen stock solution. The concentration of calcium chloride is 1 mol / L, the concentration of diammonium hydrogen phosphate is 0.6 mol / L, the concentration of NaOH is 0.1 mol / L and 1 mol / L, and the collagen stock solution is bovine Achilles tendon type I collagen purchased from Chengdu Kele Biological Products Co., Ltd., which is the collagen reaction stock solution with a concentration of 2w%.

[0047] Step 2: Preparation of dynamically mineralized collagen solution: Add 8.4 mL of calcium chloride and diammonium hydrogen phosphate solution to 5 mL of 2% type I collagen stock solution. After mineralization for 1 h, adjust the pH to 7.4 using NaOH solution. First, use 1 mol / L NaOH solution for coarse adjustment, then use 0.1 mol / L NaOH solution for fine adjustment. Stir thoroughly and maintain for 1 h. Make up the volume to 14 mL and maintain at pH 7.4 for 48 h. Then, centrifuge at 5000 rpm to collect the composite material, discard the supernatant, and obtain the mineralized collagen solution.

[0048] Step 3: Preparation of scaffold with dynamic ion concentration: Take the lower layer of mineralized collagen solution, shake it evenly, drop it into the mold, freeze-dry it at -20℃ for 24 hours to form the scaffold, and then freeze-dry it in a freezer vacuum machine for 24 hours to obtain the scaffold with dynamic ion concentration.

[0049] Comparative Example 2

[0050] A method for improving the properties of mineralized collagen based on discretely increasing ion concentration includes the following steps:

[0051] Step 1: Preparation of the reaction stock solution: The reaction stock solution includes calcium chloride, diammonium hydrogen phosphate, NaOH solution, and collagen stock solution. The concentration of calcium chloride is 1 mol / L, the concentration of diammonium hydrogen phosphate is 0.6 mol / L, the concentration of NaOH is 0.1 mol / L and 1 mol / L, and the collagen stock solution is bovine Achilles tendon type I collagen purchased from Chengdu Kele Biological Products Co., Ltd., which is the collagen reaction stock solution with a concentration of 2w%.

[0052] Step 2: Preparation of dynamically mineralized collagen solution: Add 2.1 mL of calcium chloride and diammonium hydrogen phosphate solution to 5 mL of 2% type I collagen stock solution. After mineralization for 1 h, adjust the pH to 7.4 using NaOH solution. First, use 1 mol / L NaOH solution for coarse adjustment, then use 0.1 mol / L NaOH solution for fine adjustment. Stir thoroughly and maintain for 1 h. Make up the volume to 14 mL and maintain at pH 7.4 for 48 h. Then, centrifuge at 5000 rpm to collect the composite material, discard the supernatant, and obtain the mineralized collagen solution.

[0053] Step 3: Preparation of scaffold with dynamic ion concentration: Take the lower layer of mineralized collagen solution, shake it evenly, drop it into the mold, freeze-dry it at -20℃ for 24 hours to form the scaffold, and then freeze-dry it in a freezer vacuum machine for 24 hours to obtain the scaffold with dynamic ion concentration.

[0054] Figure 2 The images shown are SEM images of Comparative Examples 1-2 and Examples 1-3. Group A1 represents Comparative Example 1, where mineral ions were added once and the total amount added was 8.4 mL. A1-1, A1-2, and A1-3 are SEM images and progressively enlarged views of Comparative Example 1, with the scale shown in the figure. Group A2 represents Comparative Example 2, where mineral ions were added once and the total amount added was 2.1 mL. A2-1, A2-2, and A2-3 are SEM images and progressively enlarged views of Comparative Example 2. Group B1 represents Example 1, where mineral ions were added twice and the total amount added was 8.4 mL. B1-1, B1-2, and B1-3 are SEM images and progressively enlarged views of Example 1. Group B2 represents Example 2, where mineral ions were added four times and the total amount added was 8.4 mL. B2-1, B2-2, and B2-3 are SEM images and progressively enlarged views of Example 2, with the scale shown in the figure. Group B3 indicates that the mineral ion concentration was added twice, with a total added volume of 4.2 mL, which is Example 3. B3-1, B3-2, and B3-3 are SEM images and progressively enlarged views of Example 3, with the scale shown in the figure. Figure 2 It can be seen that when added in multiple batches, the resulting mineral content is high, the mineralization is relatively uniform, and there is not too much complex mineral structure.

[0055] Figure 3 The mechanical Young's modulus diagrams for Comparative Examples 1-2 and Examples 1-3 are derived from... Figure 3 It can be seen that Examples 1-3, i.e., the discrete ion addition method, can effectively improve the Young's modulus of the mineralized collagen scaffold, increase the stiffness of the scaffold, and more closely resemble the mechanical properties of natural bone tissue. Moreover, comparing Example 1 and Comparative Example 1, it can be seen that when the number of additions is 2, the mechanical stiffness is the best, and the Young's modulus can be improved by about 21% compared to the method of adding ions once, which is closest to that of real bone.

[0056] Figure 4 The infrared spectra of Comparative Examples 1-2 and Examples 1-3 are shown, with 560 cm⁻¹ as the focal length. -1 and 600cm -1The absorption peak for phosphate ions indicates the presence of the mineral hydroxyapatite. A larger integrated area represents a higher concentration of hydroxyapatite, further characterizing the mineral composition of the comparative and example samples. Table 1 shows the integration of the Fourier transform infrared spectra of Examples 1-3 and Comparative Examples 1-2 within their respective characteristic peaks. Table 1 shows that Examples 1-3 produced more hydroxyapatite than Comparative Example 1. This demonstrates that when the total concentration of added ions remains constant, dynamically increasing the discrete ion concentration can produce more hydroxyapatite. Specifically, Comparative Example 1 showed an absorption peak at 560 cm⁻¹. -1 and 600cm -1 The corresponding characteristic peak is missing at this point, making integration impossible.

[0057] Table 1 shows the integral values ​​of the corresponding mineral characteristic peaks for Examples 1-3 and Comparative Examples 1-2.

[0058] Group Integral area Integral range Comparative Example 1 / / Comparative Example 2 7.749 607-568 Example 1 9.129 607-565 Example 2 12.583 605-565 Example 3 17.771 605-565

[0059] Therefore, the present invention adopts the above-mentioned method of improving the performance of mineralized collagen based on discrete increase of ion concentration. By dynamically controlling the ion concentration, the nonlinear process of natural bone mineralization is simulated, which enables collagen to attach more inorganic minerals. At the micron scale, the prepared mineralization degree is higher; at the macro scale, the mineralized collagen has better mechanical properties and more minerals, which can provide technical support for the preparation of multi-scale biomimetic bone matrix materials.

[0060] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.

Claims

1. A method for improving the properties of mineralized collagen based on discretely increasing ion concentration, characterized in that: Includes the following steps: Step 1: Prepare the reaction stock solution; Step 2: Prepare a dynamically mineralized collagen solution; Step 3: Prepare a scaffold with dynamically changing ion concentration.

2. The method for improving the properties of mineralized collagen based on discretely increasing ion concentration according to claim 1, characterized in that: The reaction stock solution in step one includes calcium chloride, diammonium hydrogen phosphate, NaOH solution, and collagen stock solution. The concentration of calcium chloride is 0.5-1 mol / L, the concentration of diammonium hydrogen phosphate is 0.5-1 mol / L, the concentration of NaOH is 0.1-1 mol / L, and the collagen stock solution is type I collagen with a concentration of 1-5 wt%.

3. The method for improving the properties of mineralized collagen based on discretely increasing ion concentration according to claim 1, characterized in that: The specific operation of step two is as follows: Add calcium chloride and diammonium hydrogen phosphate solution to type I collagen stock solution for mineralization, repeat 2-4 times, and add the same amount of calcium chloride and diammonium hydrogen phosphate solution each time. Adjust the pH with NaOH solution, stir thoroughly, then centrifuge to collect the composite material, discard the supernatant, and obtain the mineralized collagen solution.

4. The method for improving the properties of mineralized collagen based on discretely increasing ion concentration according to claim 1, characterized in that: The specific operation of step three is as follows: take the lower layer of mineralized collagen solution, shake it evenly, drop it into the mold, freeze-dry it in the refrigerator to form a shape, and then freeze-dry it in a freezer vacuum machine to obtain a scaffold with dynamic ion changes.

5. The method for improving the properties of mineralized collagen based on discretely increasing ion concentration according to claim 3, characterized in that: In step two, the amount of type I collagen stock solution used is 5-10 mL, and the amount of calcium chloride and diammonium hydrogen phosphate solution added each time is 2-5 mL. Each time calcium chloride and diammonium hydrogen phosphate solution is added, mineralization is required for 1-2 hours. The pH is adjusted to 7-8 with NaOH solution, and after thorough stirring, it is kept for 1-2 hours. The volume is then adjusted to 10-15 mL, and it is kept at pH 7-8 for 36-48 hours. After mineralization is completed, centrifugation is performed at a speed of 4000-6000 rpm.

6. The method for improving the properties of mineralized collagen based on discretely increasing ion concentration according to claim 3, characterized in that: In step two, when adjusting the pH, first use a high-concentration NaOH solution for coarse adjustment, and then use a low-concentration NaOH solution for fine adjustment.

7. The method for improving the properties of mineralized collagen based on discretely increasing ion concentration according to claim 4, characterized in that: In step three, the temperature in the refrigerator is -15 to -20°C, and the freeze-drying time is 24-36 hours. Alternatively, the freeze-drying time is 24-36 hours in a freezer vacuum chamber.

Citation Information

Patent Citations

  • Multi-stage biomimetic mineralized collagen-based skull repair implant and preparation method thereof

    CN110101487A

  • Phosphate-mediated apatite self-assembly method and application thereof

    CN114668891A

  • Mineralized collagen preparation method based on dynamic crosslinking and obtained mineralized collagen

    CN118286511A

  • Multifunctional mineralized collagen with uniform layered structure as well as preparation method and application of multifunctional mineralized collagen

    CN120037457A

  • Mineralized collagen material, preparation method therefor, and application thereof

    US20240358890A1